2019
DOI: 10.5001/omj.2019.90
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Liver Disease: Know More

Abstract: Cystic fibrosis (CF) is a multisystem disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. CFTR is expressed in the apical surface of cholangiocytes. Homozygous CFTR gene mutation results in viscous and acidic bile secretions secondary to deficient surface fluid and bicarbonate efflux. Viscous, inspissated bile causes ductular obstruction and hepatotoxicity from retained bile components, leading to fibrosis and ultimately cirrhosis, known as CF liver disease (CFLD). CFLD is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
4
0
1
Order By: Relevance
“…Furthermore, the bile pH of CF rabbits was lower than that of WT (Fig. 2A ), consistent with the knowledge obtained from CF animal models ( 29 , 30 ) and CF patients ( 28 ). The levels of total serum BAs in the CF rabbits were lower than that in the WT animals (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the bile pH of CF rabbits was lower than that of WT (Fig. 2A ), consistent with the knowledge obtained from CF animal models ( 29 , 30 ) and CF patients ( 28 ). The levels of total serum BAs in the CF rabbits were lower than that in the WT animals (Fig.…”
Section: Resultssupporting
confidence: 89%
“…It is known that BA dysregulation contributes to CFLD ( 27 ). One of the first event in CFLD pathogenesis is the reduced bile flow due to the increased bile viscosity ( 28 ). Indeed, the bile from all CF rabbits that were examined ( n = 4, 6 weeks old) was thick and tenacious ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bile acid (BA) dysregulation contributes to the development of CFLD ( 48 ). BA-targeted metabolomics analysis showed that most BA species were altered in either the bile ( Supplemental Figure 6 ) or liver samples ( Figure 6 ) of the CF rabbits, compared with those of WT animals.…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional approaches involve optimizing caloric content up to 150% of estimated daily calories with emphasis on a high fat diet [43] , [44] , dietary supplementation of fat-soluble vitamins and medium chain fatty acids, and pancreatic enzyme supplementation [1] . Protein supplementation can be a balancing act because increased protein in severe CFLD patients can precipitate decompensation [45] . During periods of undernutrition, oral calorie supplements in conjunction with a meal or as a snack between meals [46] can prove vital in rehabilitation.…”
Section: Cfld and General Endocrine Considerationsmentioning
confidence: 99%